The Effect Of Warm Water Compress On Pain In Phlebitis - Ni Komang Juliari; Ismunandar Wahyu Kindang; Ni Nyoman Elfiyuna (KEWINUS: Jurnal Keperawatan dan Kesehatan, 2025)
Phlebitis is an inflammation of the vein caused by chemical irritation or improper needle insertion, resulting in pain and discomfort for patients. Warm compress application can facilitate vasodilation by improving blood circulation in the affected vein. This study aimed to analyze the effect of warm compresses on pain among inpatients with phlebitis at Anutapura Hospital, Palu. The research employed a pre-experimental design with a one-group pretest posttest approach. The study population consisted of all patients diagnosed with phlebitis from January to December 2024, totaling 40 individuals, with a sample of 7 respondents selected using Respondent-Driven Sampling. The results showed that prior to the intervention, most respondents experienced severe pain, whereas after receiving warm compresses, the majority reported a reduction to mild pain. The Wilcoxon test revealed an Asymp. Sig. (2 tailed) value of 0.015 (p < 0.05), indicating a significant effect of warm compresses on pain reduction in patients with phlebitis. These findings highlight that warm compresses can serve as a simple and effective non-pharmacological intervention to alleviate pain in phlebitis patients.